Patterns of chemotherapy‐induced toxicities and outcome in children and adolescents with metastatic rhabdomyosarcoma: A report from the Children's Oncology Group. Issue 9 (23rd March 2017) - Gupta, Abha A.; Chi, Yueh‐Yun; Anderson, James R.; Lyden, Elizabeth; Weigel, Brenda; Arndt, Carola; Meyer, William H.; Rosenberg, Abby; Hawkins, Douglas S.
Abstract: Background: We sought to determine whether adolescents with metastatic alveolar rhabdomyosarcoma (ARMS) or embryonal RMS (ERMS) had a different event‐free survival (EFS) compared with younger patients, and to identify treatment‐related factors (adverse events, AEs) that may be associated with differences in outcome. Methods: The prevalence of AEs in adolescents older than 13 years was compared with that in patients less than or equal to 13 years of age (Fisher exact test) in patients enrolled onto ARST0431. EFS by age and histology was compared by log–rank test. Results: Of 109 patients, 60 (55%) were older than 13 years; they were more likely to have nausea (17 vs. 4%, P = 0.06) and pain (20 vs. 6%, P = 0.05) compared with younger patients. Adolescents were less likely to complete therapy (63 vs. 76%) and more likely to have unplanned dose modifications outside of protocol guidelines (23 vs. 2.7%). The 3‐year EFS was 26% (95% confidence interval [CI]: 15–38) for adolescents compared with 46% (95% CI: 32–60) for those less than or equal to 13 years ( P = 0.011). Forty‐two (59%) adolescents with ARMS had a 3‐year EFS of 13% (95% CI: 2–23) compared with 30% (95% CI: 10–51) for those less than or equal to 13 years ( P = 0.032). EFS was comparable between older and younger patients with ERMS (64 vs. 55%, P = 0.53). Conclusions: Although there was a significant difference in EFS and protocol compliance by age, the differences in age‐related toxicity are unlikely to account for this. Observed differences in pain and nausea by age could be real or be dependent on patient reporting of symptoms. Future studies in RMS should include patient‐reported outcomes to better evaluate health‐related quality of life.